DNA Repair and Signaling in Immune-Related Cancer Therapy - Kakoti, Sangeeta; Sato, Hiro; Laskar, Siddhartha; Yasuhara, Takaaki; Shibata, Atsushi (Frontiers in Molecular Biosciences, 2020)
Cancer therapy using immune checkpoint inhibitors (ICIs) is a promising clinical strategy for patients with multiple types of cancer. The expression of programmed cell death ligand-1 (PD-L1), an immune-suppressor ligand, in cancer cells is a factor that influences the efficacy of ICI therapy, particularly in the anti-programmed cell death protein-1 (PD-1)/PD-L1 antibody therapy. PD-L1 expression in cancer cells are associated with tumor mutation burden including microsatellite instability because the accumulation of mutations in the cancer genome can produce abnormal proteins via mutant mRNAs, resulting in neoantigen production and HLA-neoantigen complex presentation in cancer cells. HLA-neoantigen presentation promotes immune activity within tumor environment; therefore, known as hot tumor. Thus, as the fidelity of DNA repair affects the generation of genomic mutations, the status of DNA repair and signaling in cancer cells can be considered prior to ICI therapy. The database analysis showed that tumor samples harboring mutations in any non-homologous end joining, homologous recombination, or DNA damage signaling genes exhibit high neoantigen levels. Alternatively, an urgent task is to understand how the DNA damage-associated cancer treatments change the status of immune activity in patients because multiple clinical trials on combination therapy are ongoing. Recent studies demonstrated that multiple pathways regulate PD-L1 expression in cancer cells. Here, we summarize the regulation of the immune response to ICI therapy, including PD-L1 expression, and also discuss the potential strategies to improve the efficacy of ICI therapy for poor responders from the viewpoint of DNA damage response before or after DNA damage-associated cancer treatment.